2023
DOI: 10.3390/nano13050789
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Laser-Induced Nano-Joining of Volatile Tellurium Nanotube Memristor

Abstract: Nanowire/nanotube memristor devices provide great potential for random-access high-density resistance storage. However, fabricating high-quality and stable memristors is still challenging. This paper reports multileveled resistance states of tellurium (Te) nanotube based on the clean-room free femtosecond laser nano-joining method. The temperature for the entire fabrication process was maintained below 190 °C. A femtosecond laser joining technique was used to form nanowire memristor units with enhanced propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Additionally, in the context of nanoparticle fusion, femtosecond lasers excel at merging nanoparticles to form larger aggregates or attaching them to diverse substrates, a capability that is increasingly vital in the advancement of sensor technology [80,83]. In addition, femtosecond laser irradiation has proven to be a transformative tool for enhancing nanojoining in memristor and nanoelectronics devices [79,84].…”
Section: Femtosecond Laser Nanojoiningmentioning
confidence: 99%
“…Additionally, in the context of nanoparticle fusion, femtosecond lasers excel at merging nanoparticles to form larger aggregates or attaching them to diverse substrates, a capability that is increasingly vital in the advancement of sensor technology [80,83]. In addition, femtosecond laser irradiation has proven to be a transformative tool for enhancing nanojoining in memristor and nanoelectronics devices [79,84].…”
Section: Femtosecond Laser Nanojoiningmentioning
confidence: 99%
“…223 Recently, Yu et al demonstrated that laser irradiation of a single Te nanotube-based memristor could lead to a change in memristive performance to capacitively coupled memristor behavior. 104 With various advantages of the nanojoining techniques, 217,224 we are expecting that nanojoining methods to controllably fabricate and engineer the memristor This journal is © The Royal Society of Chemistry 2024 devices will be further explored and more methods will also be put forward.…”
Section: Nanojoiningmentioning
confidence: 99%
“…Yu et al reported a Te nanotube memristor welded to aerosol-printed silver electrodes. 104 The switching mechanism is related to the formation of a TeO x layer. Recently, Wang reported a volatile memristor based on 2D Te nanoflakes.…”
Section: D/3d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanowire interconnection strategies make these arrangements more permanent and mitigate the issue of contact resistance. Nanojoining has been demonstrated in the literature by localized surface melting via light-based resonance techniques such as radiative laser-ablation [56][57][58][59][60] or plasmonic confinement [61,62] across a broad population of overlapping nanowires. Given their small diameter, thin film metallic deposition can also enable functional interconnection between nanowire components, as demonstrated between individual wires under an electron microscope [63] or across a randomly oriented array [64].…”
Section: Introductionmentioning
confidence: 99%